How is the Compensation of Employees? - Elfira Fawzia; Firman Pribadi (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2021)
The compensation system is very critical and sensitive in the company. So that not a few companies are experiencing difficulties due to compensation that appears not implemented properly. The primary purpose of this study was to determine the remuneration system at PKU Aisyiyah Hospital Jepara. This study uses observation and in-depth interviews with selected respondents to collect data and analyzes with a qualitative approach using an action research design. The qualitative case study used purposive sampling involving nine people directly involved in the compensation process: three directors, three heads of general and finance divisions, and three finance staff. Some hospitals have not implemented the 2017 Permendiknas, but they have generally implemented several remuneration principles. This research has implications for the process of providing remuneration to hospital employees and recommendations for hospital managers to improve the application of remuneration according to PERMEN 2017.